Deflation and Public Finances : Evidence from the Historical Records - End, Nicolas (IMF Working Papers; Working Paper ;, 2015)
This paper examines the impact of deflation on fiscal aggregates. With deflation relatively rare in modern history, it relies mostly on the historical records, using a dataset panel covering 150 years and 21 advanced economies. Empirical evidence shows that deflation affects public finances mostly through increases in public debt ratios, reflecting a worsening in interest rate-growth differentials. On average, a mild rate of deflation increases public debt ratios by almost 2 percent of GDP a year, this impact being larger during recessionary deflations. Using a simulation model that accounts for composition effects and price expectations, we also find that, for European countries, a 2 percentage point deflationary shock in both 2015 and 2016 would lead to a deterioration in the primary balance of as much as 1 percent of GDP by 2019.